PENGARUH BRAND IMAGE DAN KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN DI APOTEK DENGAN LAYANAN DOKTER KELUARGA - Putri, Natalia Christiani; Fristiohady, Adryan; Ruslin, Ruslin; Wahyuni, Wahyuni; Akib, Nur Illiyyin (LPPM Hang Tuah Pekanbaru, 2025)
The continuous growth in the number of pharmacies in Kendari City has intensified competition in this business sector. In such a competitive landscape, brand image and service quality become crucial factors influencing consumer preferences when choosing a pharmacy. Apotek PS, which has been serving the Kendari community for over a decade, is recognized for its strong brand reputation and reliable service standards. This study aims to explore the impact of brand image and service quality on customer loyalty at Apotek PS. Data were collected through a Google Form-based questionnaire completed by 100 customers who had visited at least twice. The collected data were then analyzed using descriptive statistical methods and the Structural Equation Modeling (SEM) approach with the assistance of SmartPLS software. The findings of this study confirm that both brand image and service quality contribute positively and significantly to customer loyalty. Together, these two variables account for 78.4% (indicating a strong influence) of customer loyalty, with a Q-squared value of 0.772, signifying a high level of predictive accuracy. Furthermore, the PLS model evaluation demonstrates an acceptable level of model fit. Based on the Cross-validated Predictive Ability Test, the PLS model exhibits a higher predictive accuracy than the IA and LM models, leading to the conclusion that the PLS model performs better in predicting customer loyalty.